Evaluation of Production Peak of Laying Hens Strain Lohman Brown in CV. Lawu Farm Malang - Yolifia Rahma Milenia; Sri Pantja Madyawati; Agung Budianto Achmad; Ratna Damayanti (Universitas Airlangga, 2022)
Background: The productivity of laying hens is a key measurement in the laying hens business. One of the targets for laying hens is to achieve peak production. The optimal peak production period is necessary to attain the maximum profit. Purpose: To determine the productivity of laying hens strain Lohman Brown aged 25-49 weeks at CV. Lawu Farm Malang Regency as an evaluation of the peak production period. Case Analysis: The descriptive method with the case study technique was used. Primary data were obtained from observations by participating in direct livestock activities, interviews, and documentation, and secondary data were obtained from literature studies. The variables observed in this study were Hen Day Production, Feed Conversion Ratio, egg weight, and mortality. Results: Observation of laying hens productivity in CV. Lawu Farm showed that 71.42% of Hen Day Production value of the full cages had met the target with HDP of more than 92%, while 28.58% did not reach the peak production target by only getting HDP less than 90%. The FCR value was 2.4 – 2.15, the average egg weight wais 63.03 grams/egg, and the mortality was ≤3%. Conclusion: The productivity of laying hens of the Lohman Brown strain aged 24-59 weeks at CV. Lawu Farm has met production standards in terms of HDP, FCR, egg weight, and mortality.